Rational use of immunodiagnostic tools for tuberculosis infection: guidelines and cost effectiveness studies - Amicosante, Massimo; Ciccozzi, Massimo; Markova, Roumiana (The New microbiologica, 2010)
Tuberculosis (TB) remains a public health challenge and its control requires the use efficient diagnostic tools. Mycobacterium tuberculosis (MTB) elicits a strong immune response upon infection, a phenomenon measured by the old tuberculin skin test (TST). However, this test has many limitations and a high rate of positivity in BCG-vaccinated subjects. Recent studies have identified several MTB-antigens for diagnostic use, including the ESAT-6 and CFP-10 proteins. Based on these antigens, one of the most significant developments in the diagnostic armamentarium for TB has been the assays based on IFN- determination (IGRAs). The assays stem from the principle that T-cells of infected individuals produce IFN-gamma when they re-encounter the MTB antigens in vitro and this can be measured by a conventional ELISA test. The evaluation of IGRAs in different clinical settings showed many advantages over TST. The worldwide diffusion of IGRAs has increased the knowledge on their clinical use and a number of guidelines have been devised for their application. The two-step approach (first using TST followed by IGRA for confirmation) is the most favored strategy for IGRA-use in the general population, while the use of IGRAs alone is suggested in particular clinical settings and/or patient groups. Even if these tests are still costly there are a number of cost effective advantages in the "targeted" use of IGRAs over the TST. The work we present summarises all these aspects.